Побудування моделі для розрахунку водо-водяного теплообмінника у складі мутьтипаливного котельного агрегату - Каверцев, Валерій Леонідович; Дягілєв, Вадим Олександрович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Метою даної статті є створення напряму для розробки комплексної програми розрахунку мультипаливних котельних агрегатів. У статті пропонується розрахунок водо-водяного теплообміннику який входить до складу мультипаливного котла. Представлений варіант логічної блок-схеми даного розрахунку можна буде використовувати для розробки варіантів конструкцій мультипаливних котельних агрегатів за допомогою програмних комплексів в комп’ютерному середовищі.

It was shown that an efficient use of fuel and energy resources provides a regular power supply for the State. The metallurgy industry is the main sector of industry for which the irrational use of fuel is an urgent problem. Serial boiler units that are used by metallurgy companies were designed for the natural gas and black oil burning only and as a result these fail to meet current requirements. Now, we design new multifuel boiler units that can operate using two and even more types of fuel and we also upgrade and reconstruct already available boiler units of this type. We suggest the solutions for complicated engineering problems in the form of different computations done to define optimal characteristics for the boiler equipment. This scientific paper delves into the design of the water-water heat exchanger that forms an integral part of the multifuel boiler unit. This heat exchanger can also be used for the reconstruction of already available boilers. The developed logic block diagram is intended for the computations done to design the water-water heat exchanger and it will be used by the software package for the computation of the separation in the multifuel boiler unit to simplify computations. It was noted in the conclusions that the model algorithm and logframe would enable the computation of an ample amount of the elements and circuitry for the multifuel boiler equipped with the water-water heat exchanger.
Model construction to design the water-water heat exchanger as an integral part of the multifuel boiler unit
Keywords: енергетика; математична модель; power engineering; mathematical model